2021
DOI: 10.1186/s12891-020-03941-8
|View full text |Cite
|
Sign up to set email alerts
|

Low BASDAI score alone is not a good predictor of anti-tumor necrosis factor treatment efficacy in ankylosing spondylitis: a retrospective cohort study

Abstract: Background The purpose of this study was to determine the prevalence of high disease activity as measured using the Ankylosing Spondylitis Disease Activity Score (ASDAS) in ankylosing spondylitis (AS) patients who nonetheless have low Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) scores after anti-tumor necrosis factor (TNF) treatment. Its clinical impact on anti-TNF survival was also investigated. Methods We conducted a single-centre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The Kruskal Wallis test was used for comparison of the suicidal ideation scale scores between the multiple independent groups. The level of statistical significance in nonparametric multiple comparisons was determined with the Bonferroni correction (p scores[35]. Based on the parametric distribution of the data, psychometric assessment scales of remission/mild and moderate RA patients were compared with Students t-test and AS patients at remission or non-remission were compared with Mann-Whitney U test.…”
mentioning
confidence: 99%
“…The Kruskal Wallis test was used for comparison of the suicidal ideation scale scores between the multiple independent groups. The level of statistical significance in nonparametric multiple comparisons was determined with the Bonferroni correction (p scores[35]. Based on the parametric distribution of the data, psychometric assessment scales of remission/mild and moderate RA patients were compared with Students t-test and AS patients at remission or non-remission were compared with Mann-Whitney U test.…”
mentioning
confidence: 99%
“…Still, quantification of osteoblastic activity demonstrated that the SUV max decreased, stayed similar, or, on rare occasion, showed only a minor increase. These data indicate that the magnitude of the treatment effect at the structural level, as assessed by imaging, may not necessarily reflect the magnitude of its effect on treatment outcomes, which might depend on the tool used to assess global disease activity or on the effect of comorbidities, such as concomitant fibromyalgia (28–31). Another explanation for this observation may be that, in some patients, treatment with TNFi but also with other bDMARDs needs >6 months to reach its full potency with regard to clinical outcomes and structural changes (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…However, it's worth noting that there are other markers of plasma atherogenicity, such as AIP [ 30 ]. Firth, the Ankylosing Spondylitis Disease Activity Score (ASDAS) which is a more disease-specific and objective disease activity index than ESR and CRP levels, could not be utilized in our study [ 31 ]. Another limitation of our study is the relatively short follow-up duration, highlighting the importance of conducting further studies with longer observation periods.…”
Section: Discussionmentioning
confidence: 99%